Cobalt/nitrogen codoped carbon nanosheets derived from catkins as a high performance non-noble metal electrocatalyst for oxygen reduction reaction and hydrogen evolution reaction. Issue 71 (27th November 2020) - Song, Luting; Chang, Jinquan; Ma, Yanhong; Tan, Xinghua; Xu, Yuanqing; Guo, Limin; Chen, Zhexue; Zhao, Tingqiao; Li, Yueqi; Liu, Yanlin; Zhang, Yong; Chu, Weiguo
Abstract : We prepare highly efficient NPM catalysts of cobalt and nitrogen co-doped carbon nanosheets for oxygen reduction and hydrogen evolution reactions using catkin biomass. Abstract : Novel energy devices which are capable of alleviating and/or solving the energy dilemma such as overall water splitting and fuel cells require the development of highly efficient catalysts, especially cheap high performance non-precious metal (NPM) catalysts. Here, we prepare highly efficient NPM catalysts of cobalt and nitrogen codoped carbon nanosheets (Co/N–CNSs) for oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) using harmful environment-polluting waste of biomass catkins as carbon precursors via a mild mechanical exfoliation and chemical process which is facile, low-cost, environmentally friendly and up-scalable. Compared with a commercial platinum-based catalyst (commercial 20% Pt/C), the Co/N–CNS electrocatalysts show outstanding ORR activity, acceptable HER activity and long term stability with an onset potential of 0.92 V versus the reversible hydrogen electrode ( vs. RHE) and a half-wave potential of 0.83 V vs. the RHE in alkaline electrolytes. The excellent performance is closely related to the presence of abundant CoN x active sites. This work offers a novel and effective approach for preparing highly efficient ORR and HER NPM electrocatalysts from waste biomass materials.